2178. Detection of Key Potential Healthcare Pathogens Using Periodic Point Prevalence Surveillance. (26th November 2018) - Schora, Donna; Vernon, Michael O; Fisher, Adrienne; Kufner, Bridget; Shah, Mona; Lim, Rachel; Komutanon, Vanida; Bockoven, Crystal; Thomson, Richard; Peterson, Lance; Singh, Kamaljit
Abstract: Background: Surveillance for asymptomatic carriage of multidrug-resistant (MDR) pathogens is useful to determine the burden of these organisms and help guide infection prevention strategy. We currently perform surveillance cultures for Gram-negative multidrug-resistant pathogens (GNMDR) in the ICUs on a monthly basis. We added a quarterly point prevalence survey to all hospital units for these and other key pathogens over one year to determine whether our program should expand beyond the ICU and include other organisms. Methods: Rectal samples were collected quarterly for 1 year starting June 2016 at NorthShore University HealthSystem, a four-hospital, 789 bed system. All hospitalized patients present on the day of the point prevalence testing had a double-headed rectal swab collected. One swab was plated to VACC agar (Remel) for culture of GNMDR and VRE, and the second was plated to CCFAHT (Anaerobe Systems) for C. difficile (Cdif) culture. All samples were collected on a specified day at each of our 4 hospitals, one hospital per week, and sent to the central microbiology lab for processing. Testing for GNMDR included the following pathogens: Carbapenem-resistant Enterobacteriaceae (CRE), ESBLs, and Gram negative organisms susceptible to ≤2 drug classes. Results: A total of 987 surveillance samples were collected. The number of patients with MDR in the ICU vs. non-ICU units is described in Table 1. There was an 11% greater difference in the percentage of patients colonized with GNMDR and Cdif in non-ICU patients compared with ICU patients ( P = 0.006). An important discovery was three patients colonized with CRE outside the ICU that were previously unknown. The burden of ESBL, VRE and Cdif carriage was also greater outside the ICU. Conclusion: The point prevalence surveillance uncovered a significant amount of MDRs in our non-ICU units, particularly three CREs that were previously unknown. These results suggest there is a large burden of MDR organisms outside the ICU. Disclosures: All authors: No reported disclosures.